2004
DOI: 10.1097/01.yic.0000113105.67404.5f
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain during long-term treatment with olanzapine: a case series

Abstract: The aim of this study was to assess the prevalence of weight gain during long-term treatment with olanzapine under routine conditions. Weight changes in a sample of 27 outpatients with schizophrenic or schizoaffective disorder were assessed over a mean duration of treatment of 22 months (6-42 months). Treatment with olanzapine was started anew or switched from a conventional antipsychotic drug. Eighteen (66.7%) patients gained more than 7% of their initial body weight. Mean weight gain was 9.2 kg over the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…These profiles of reasons to switch are fully in line with pharmacological and clinical data on these three drugs (e.g. Allison et al, 1999;Davis et al, 2003;Tandon and Jibson, 2003;Haberfellner and Rittmannsberger, 2004;Malla et al, 2004;Mortimer, 2004;Mortimer et al, 2004;Peuskens, 2004;Brown and Estoup, 2005;Jayaram and Hosalli, 2005;Azorin et al, 2006;Davis, 2006) as well as with findings from another investigation in routine treatment (Lieberman et al, 2005).…”
Section: Discussionsupporting
confidence: 61%
“…These profiles of reasons to switch are fully in line with pharmacological and clinical data on these three drugs (e.g. Allison et al, 1999;Davis et al, 2003;Tandon and Jibson, 2003;Haberfellner and Rittmannsberger, 2004;Malla et al, 2004;Mortimer, 2004;Mortimer et al, 2004;Peuskens, 2004;Brown and Estoup, 2005;Jayaram and Hosalli, 2005;Azorin et al, 2006;Davis, 2006) as well as with findings from another investigation in routine treatment (Lieberman et al, 2005).…”
Section: Discussionsupporting
confidence: 61%
“…The finding that, during chronic treatments, weight gain in olanzapine‐treated patients might trend towards a plateau within the first year of treatment and was more sustained during the early phase of treatment was also confirmed in retrospective or prospective head‐to‐head comparisons with haloperidol and/or risperidone (32–34). Moreover, three studies demonstrated that, as happens with both aripiprazole and clozapine, lower baseline body weight and/or BMI were associated with a greater risk of weight gain in either olanzapine‐ or risperidone‐treated patients (35–37). Direct comparisons between these two drugs identified some predictors of clinically relevant weight gain (including psychiatric comorbid conditions, number of primary care, psychiatric, and emergencies consultations, lower body weight at baseline, concomitant use of either lithium and/or valproate) (38,39).…”
Section: Results (Synthesized In Table 1)mentioning
confidence: 76%
“…Similarly or differently designed studies were also able to recognize additional patient‐ and drug‐related contributors to weight gain (such as severe psychiatric diagnoses, prevalence of negative symptoms, specific receptorial affinity) (40–42). However, such results should be interpreted conservatively because of emerging from studies with small sample sizes (35–37,39,40,42).…”
Section: Results (Synthesized In Table 1)mentioning
confidence: 99%
“…Despite sharing certain tolerability advantages over older medications, atypical antipsychotics vary markedly in other respects, notably in their metabolic effects and propensity to cause excessive weight gain. Both olanzapine and risperidone have been associated with significant weight gain (45, 46), which may become a clinically important issue in long‐term use. The results of this study were consistent with the previously reported weight gain with quetiapine treatment and, although there were increases in weight compared to placebo, the weight change did not lead to study withdrawal for any patient.…”
Section: Discussionmentioning
confidence: 99%